The influence of financial literacy and fintech payment behavior on healthy financial management behavior the mediating role of financial self-control among generation Z - Srikandi Pratama Agni Putri; Maiyaliza Maiyaliza (Universitas Nusa Cendana, 2026)
This study examines the influence of financial literacy and fintech payment behavior on healthy financial management behavior among Generation Z students, with financial self-control as a mediating variable. A quantitative approach was employed using a survey of 384 students in Cirebon. Data were analyzed using structural equation modeling to test the relationships between variables. The findings indicate that financial literacy and fintech payment behavior significantly influence healthy financial management behavior. Furthermore, financial self-control plays a crucial mediating role in strengthening these relationships. These results suggest that improving financial literacy and self-regulation are essential for developing responsible financial behavior. However, this study is limited to a specific geographic area, which may affect the generalizability of the results. Future research should expand the scope to diverse regions and include longitudinal data to better capture behavioral changes over time. Educational institutions and fintech providers should collaborate to promote financial education programs. Keywords: Financial Literacy; Fintech Payment Behavior; Generation Z; Financial Management Behavior; Financial Self-Control